Teacher-Parent Collaboration and Academic Achievements of Learners with Learning Disabilities in Bamenda II And III Council Areas Mezam Division North West Region of Cameroon - Ngwainbi Genesis Aseh; Lobti Doris Mahgeh (Journal of Innovation in Education and Social Research, 2025)
This study investigated teacher- parent collaboration and academic achievement of learners with learning disabilities in inclusive schools in Bamenda II and III Municipalities. The main objective was to find out how Teacher- Parent collaboration affects academic achievement. Specific objectives were to find out how teacher- parent communication affects academic achievement, to assess how parental engagement affects academic achievement. To determine the extent to which Parent Teacher Association (PTA) support affects academic achievement of learners with learning disabilities in these Municipalities. Theoretically, three theories were reviewed, Maslow‟s Hierarchy of needs theory (1954-1971) Lev Vygotsky‟s constructivist learning theory (1896-1935) and Joyce Epstein‟s six steps theory of family involvement (1995). The population of the study was made up of inclusive schools in Bamenda II and III Council Areas. Accessible population comprised of three inclusive schools in these Bamenda. The sample size was made up of 58 respondents, Questionnaires were used to collect data from teachers and parents. The sampling technique used was the snowball sampling technique. The method of data analysis was inferential statistics. Meanwhile the statistical parametric test in the statistical package for social science (SPSS) version 26 was used. The results revealed that, there was a significant relationship between teacher parent communication and academic achievement of learners with learning disabilities. Also, the findings showed that there was a significant relationship between parental engagement in the education of learners with learning disabilities and their academic achievement. Another finding revealed that Parent Teacher Association is very important and plys a very important role in the life of learners with learning disabilities and that frequent meetings between parents and teachers of learners with learning disabilities can have a positive impact on the academic achievement of these children. Based on these findings, some recommendations were made that administrators should provide PTA with resources for their activities and policy makers should create policies that will involve teachers and parents, The authorities of the Municipalities should equally allocate funds and support programs and initiatives that foster teacher-parent programs. PTA should provide funds, recruit and train inclusive teachers for inclusive schools. Workshops and seminars should be organized where parents and teachers of these learners would be trained. Teachers and parents should have effective and frequent communication during the children‟s learning process. Parents of learners with learning disabilities should actively participate in school events and constantly supply their children with school needs. Prepare convenient reading spaces for their Children and assist children with their home works.